Theorising domestic violence and work: where are we now and where to next?. (2nd October 2022) - Weatherall, Ruth
ABSTRACT: The sentiments 'it's just good business' and 'it's the right thing to do' are commonly heard when discussing workplace domestic violence provisions. These two statements represent two divergent ways of theorising the relationship between domestic violence and work. Crucially, these alternate theories shape how domestic violence and work are discussed, who takes responsibility for domestic violence in and through the workplace and access to, and equality of support, victims receive from their workplaces. This research insight delves into the current theorising of the relationship between domestic violence and work, focusing on the business case, feminist perspectives, and a decolonial approach. Each subsequent theory layers and gives us a strong idea of where we are now with theorising and where we could go next in order to improve outcomes for victims in and through the workplace.